The internal review of corporate deviance: managing crisis, conformance, and public trust - Gottschalk, Petter (De Gruyter, 2024)
"In this pioneering monograph based upon extensive primary research, Gottschalk and Hamerton explore and evaluate the developing global field of internal investigations within complex organizations. Applying an offender-based perspective, the authors explore the central role of convenience in seeking to inform, improve and develop policy and practice. A comparative interdisciplinary work, with extensive coverage of European, North American, African and Asian paradigms, The Internal Review of Corporate Deviance presents empirical fieldwork supplemented by the detailed analysis of a large number of internal reviews produced on completion of internal investigations. The aggregate research gathered considers offender motive, conformance, potential damage and recovery of the corporate social license, and convenience themes, while critically assessing investigation effectiveness and review maturity - as both successful and deficient practice. In doing so, the book presents a close analysis of the field to identify, position, and reveal the strategic role of internal review and impact of the social license on contemporary conceptions of white-collar deviance and crime. This book will be of interest to scholars of criminology, business management, law and sociology, along with practitioners and professionals within allied disciplines" --